소년범의 교화 및 재범방지를 위한 자기주도형 선도프로그램 도입 방안 - 권일성; Kwon Il-sung; 강동욱; Kang Dong-wook (소년보호연구, 2024)
Currently, Korea has entered an aging society where the population of young people is decreasing due to low birth rates, and more than 7% of the population aged 65 or older accounts for the total population. Young children and adolescents whose population is decreasing are precious members of our society. And while most of these children and teenagers are healthy, there are also delinquent youths who commit crimes by deviating from some. However, they are also adults who will belong to our society in the future. Therefore, our society should operate a system to prevent crimes against these delinquent youths and prevent recidivism by edifying and leading juvenile offenders who have already committed crimes. In addition, it is more important to rejoin the affiliation as a member of society with appropriate initiatives than to punish juvenile offenders who have already committed crimes. This is because they are still immature, incomplete, and transitional people who are becoming adults, and must be properly taught through appropriate guidance to join as members of society. On the other hand, the purpose and reason for enacting the Juvenile Act is to treat teenagers who are physically or mentally immature differently from adults. Therefore, the state recognizes juvenile crimes as misconduct or wrongdoing by lowering the level and punishes them differently from adults. This is for the purpose of the state to re-engage as a healthy member of society by edifying and leading the youth to quickly acknowledge and reflect on their mistakes rather than punishment based on the basic idea of national friendship of youth. If so, it is questionable whether Korea currently operates various and appropriate programs to educate and lead juvenile offenders to return them to school and prevent recidivism. In this respect, the state should secure sufficient budget for this sector and operate effective programs in cooperation with the professional private sector. Among the edification and leading programs to prevent the recurrence of juvenile offenders, the self-directed walking tour leading program will be one of his options.